The relationship between age and emotional intelligence in postgraduate students - Aragundi-Moncada, Juan Gabriel; Bueno-Fernández, Mario Mitsuo; Espinoza-Solís, Eduardo; Guillén-Rodríguez, Ana Priscila; Sabando García, Ángel Ramón; Lamus de Rodríguez, Tibisay Milene; Ultreras-Rodríguez, Andrés; Moreira-Choez, Jenniffer Sobeida (Frontiers in Education, 2025)
IntroductionEmotional intelligence is essential for the holistic development of students, particularly in postgraduate contexts, where academic and personal demands are higher. This study aimed to analyze the relationship between age and emotional intelligence among postgraduate students at the State University of Milagro (UNEMI). It specifically considered the dimensions of attention, clarity, and emotional repair.MethodologyThe methodological design was quantitative, non-experimental, cross-sectional, and descriptive-explanatory. The population consisted of 1,525 postgraduate students, selected through non-probabilistic sampling. Data collection was conducted using the TMMS-24, a validated instrument administered digitally with informed consent. Statistical analysis included reliability tests, Pearson correlation, and analysis of variance (ANOVA).ResultsThe findings revealed no significant differences in overall emotional intelligence across age groups. However, specific dimensions showed variations. Students over 50 years of age excelled in emotional clarity and repair, while younger students (21 to 30 years) demonstrated higher emotional attention. These variations highlight the influence of experience and maturity on specific emotional skills.ConclusionWhile global emotional intelligence remains stable across age groups, specific dimensions such as clarity and emotional repair improve with age, whereas emotional attention is higher among younger students. These results emphasize the importance of developing educational strategies tailored to the emotional characteristics of different age groups.